2023
DOI: 10.1021/acs.jafc.3c00481
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Physiological Effects of Postharvest UV Radiation on Vegetables: A Review

Abstract: Effective ultraviolet (UV) irradiation has been used as a postharvest technology to reduce decay, delay ripening, and delay senescence in crop products. In this review, the effects of UV radiation of different wavelengths and doses on physiological and phytochemical parameters in postharvest vegetables are discussed in summary, including appearance (color and texture), microbial load, respiration rate, enzymatic antioxidant system, and various bioactive compounds (phenolic compounds, carotenoids, chlorophylls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…73 The recent focus of UV applications has been put on its capability to enrich the secondary metabolites showing obvious biological activities and health benefits. 74 There are generally two ways to induce the accumulation of pharmacologically significant phytochemicals by UV, including postharvest treatments and UV exposure to plant matrices during their germination and growth process. For example, postharvest UV-B and UV-C treatments (3.6 kJ m −2 ) of table grape induced a significant increase in phenolic compounds following a storge process (28 d, 4 °C), associated with the promoted expression of the genes involved in phenylpropanoid, flavonoid, and stilbenoid pathways by UV irradiation.…”
Section: Pl Stimulusmentioning
confidence: 96%
See 1 more Smart Citation
“…73 The recent focus of UV applications has been put on its capability to enrich the secondary metabolites showing obvious biological activities and health benefits. 74 There are generally two ways to induce the accumulation of pharmacologically significant phytochemicals by UV, including postharvest treatments and UV exposure to plant matrices during their germination and growth process. For example, postharvest UV-B and UV-C treatments (3.6 kJ m −2 ) of table grape induced a significant increase in phenolic compounds following a storge process (28 d, 4 °C), associated with the promoted expression of the genes involved in phenylpropanoid, flavonoid, and stilbenoid pathways by UV irradiation.…”
Section: Pl Stimulusmentioning
confidence: 96%
“…Ultraviolet (UV) irradiation, with the wavelength ranging between 100 and 400 nm which is further subclassified into UV-A (31–400 nm), UV-B (28–315 nm), and UV-C (200–280 nm) as well as the vacuum UV (100–200 nm), has been applied to plant-based food matrices mainly as a postharvest decontamination treatment technology due to its capability to disinfect microbiological growth and to extend the shelf life . The recent focus of UV applications has been put on its capability to enrich the secondary metabolites showing obvious biological activities and health benefits . There are generally two ways to induce the accumulation of pharmacologically significant phytochemicals by UV, including postharvest treatments and UV exposure to plant matrices during their germination and growth process.…”
Section: Gaba Concentration Variability Responding To Nonthermal Stre...mentioning
confidence: 99%
“…Inactivation of microorganisms using UV light has been actively studied with mercury lamps such as low-pressure mercury lamp and medium pressure mercury lamp [ [20] , [21] , [22] ], tunable wavelength lasers [ [23] , [24] , [25] ], and light emitting diodes (LEDs). In recent years, UV-LEDs have attracted attention for utilization in a broad field such as water, food and room because the broad range of wavelengths; the compact form factor, providing design flexibility; the longevity of the effect; the adjustable output, which can be controlled by driving current; and the environmental friendliness of the approach, without production of hazardous wastes, such as mercury [ [26] , [27] , [28] ]. Evaluations of UV sensitivity is based on how the object changes in response to UV dose, which is the product of irradiance and irradiation time; therefore, it is necessary to accurately determine the irradiance of the target surface and set an appropriate irradiation time.…”
Section: Introductionmentioning
confidence: 99%
“…A recent comprehensive review demonstrated that UV light, regardless of wavelength, has some effect on increasing the level of production of phenolic compounds, including flavonoids, in fruits and vegetables. However, the magnitude of this effect is highly variable depending on the product, UV wavelength, and UV dose . While the effect of ozone is less studied, recent studies showed that extended exposure to ozone resulted in increased concentrations of phytochemicals such as quercetin in sage but a decreased total capsaicin concentration and antioxidant content in bell pepper, highlighting the fact that the effect may be plant species and dose specific. , The complex relationship between hydrogen peroxide and related reactive oxygen species and plant abiotic response is well-established.…”
mentioning
confidence: 99%